Antioxidant and biological activities of essential oil from Colombian Swinglea glutinosa (Blanco) Merr fruit - Beatriz Eugenia Jaramillo-Colorado; Flor María Palacio-Herrera; Edisson Duarte-Restrepo (Acta Scientiarum. Biological Sciences, 2020)
The objectives of this work were the study of the volatile chemical composition of essential oils (EO’s) from Swinglea glutinosa, as well as to evaluate their antioxidant, repellent and fumigant properties. The EO was obtained by hydrodistillation from the peel of the fruit, gathered in the city of Cartagena, Bolívar (Colombia). The volatile composition was analyzed by gas chromatography coupled to mass spectrometry (GC-MS). The major compounds found in S. glutinosa were germacrene D (4.8%), limonene (5.2%), a-terpineol (6.5%), b-pinene (8.5%), nerolidyl acetate (9.8%), and trans-nerolidol (34.6%). S. glutinosa showed antioxidant potential (85.8%) (IC50=142.49 µg mL-1). The EO deployed repellent activity against the Tribolium castaneum weevil at a concentration of 15.73 nL cm-1 at 2 hours of exposure (72%), while the result for the commercial repellent was 50% at the same concentration. EO from S. glutinosa displayed the best fumigant activity with LC50 of 153.4 μg mL-1 air. The essential oil from S. glutinosa can be considerated as a natural source of biocides and antioxidants.